PENGARUH BEBAN KEPENGURUSAN OSIS TERHADAP TINGKAT STRES DAN KESEHATAN MENTAL SISWA KELAS XI DI LINGKUNGAN PESANTREN MUHARRIKUNAJAH KLATEN - Mujahid, Abdur Rahman; Shobahiya, Mahasri (Yayasan Haiah Nusratul Islam, Indonesia, 2026)
This study examines the effect of organizational workload in the Student Council (OSIS) on stress levels and mental health among eleventh-grade student leaders at Muharrikunajah Islamic Boarding School, Klaten. Student organizations in boarding schools play an important role in character and leadership development, yet excessive responsibilities may create psychological pressure. The research aims to analyze the level of organizational workload, identify stress symptoms, and describe the mental health condition of OSIS administrators. A descriptive quantitative approach was employed using a survey method. Data were collected from six core OSIS administrators through a four-point Likert-scale questionnaire complemented by open-ended questions. The data were analyzed using descriptive statistics and thematic analysis. The findings indicate that the organizational workload ranges from moderate to high, particularly due to intensive activities, frequent night meetings, and limited supervisor support. Stress levels varied from low to high, with the OSIS chairman experiencing the highest stress. Although learning motivation and emotional regulation remained relatively stable, disturbances were found in daily balance and spiritual calmness. These results highlight the need for stronger supervision, proportional task distribution, and institutional support to maintain students’ mental well-being.